Surveillance of Listeria monocytogenes in food catering establishments - Maia, Carla (2014)
Surveillance of Listeria monocytogenes in RTE (Ready To Eat) Foods sampled in canteens in Lisbon area and surroundings and presentation of a case study (Listeria spp. in a Hospital kitchen.)